(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Tourism and its markets are facing unprecedented changecaused by demographic shifts, changing lifestyle, values and rapidly evolvingtechnologies across the world, Consumer trends in tourism are graduallychanging and require an appropriate response in terms of both policyformulation and investment. Customer’s attitudes are being shaped by educationand experience with major strategic implications for tourism destinations asthey demand increasingly higher standards. Karnataka being one of the mostfamous tourist destinations, it lags behind in terms of annual tourist arrivalsand has to upgrade its facilities in order to get a bigger share of the touristpie. The interest in cultural tourism, spiritualism, ‘wellness’ holidays,eco-tourism and rural tourism would tend to favor Karnataka’s tourism, providedthe state can avail of the opportunities offered to maximize its naturaladvantages in these areas but it isobserved that regional linkages, connectivity, accommodation and lack offinancial resources were the main hindrances to develop tourism inKarnataka. The development of newtourism products and destinations must be based on market research and demand,keeping the source markets and the age groups of the tourists in mind. At thesame time, the Government must develop new source markets nearer home and makeKarnataka a safer destination for tourists and family holidays. Presently, Karnataka’s tourism is truly at crossroads assuch this paper highlights the responsibility of management of touristdestinations, tourist departments, experts and government to rethink and toredesign their marketing strategies, developmental priorities to fill the gapof demand and supply and other problems of regional linkages, connectivity,accommodation and lack of financial resources for the proper development oftourism in Karnataka.